EMERGING BIOSIMILARS IN ONCOLOGY: A REVIEW - B, Lavanya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Biosimilars are the biological medicinal products that produce the therapeutic effects in the human body similar to that of inner biological molecule. Biopharmaceuticals consist of nucleic acids, amino acids, polysaccharides, or combination of all compounds. In India, the steps have been taken to manufacture biosimilars with the lowest cost and least side effects. Globally, India is one of the major developing countries in manufacturing and marketing of biosimilars. The application of biosimilar was rapidly growing in treating various disorders such as cancer, inflammatory disease, and cardiovascular diseases. For the approval of biosimilars, in vitro studies become the necessity for representing comparison to a standard biological in terms of quality for experimental studies indicating similar pharmacokinetics, efficacy, safety, and immunogenicity. Huminsulin was the first DNA-recombinant protein accepted by the US Food and Drug Administration (FDA) in 1982. As currently there are no FDA-approved biosimilars for treating breast cancer, many biologic antibodies are under investigation.